Macht Arbeit Frei? - Mędykowski, Witold (Academic Studies Press, 2021)
This book examines the forced labor of Jews in the General Government of Occupied Poland from 1939-1943. Specifically, it traces the bureaucratic understanding and use the terms "labor" and "work" in the General Government; it also examines how these terms figured in the lives of Jews, for whom "labor"''s original understanding as a means of subsistence came to be redefined as a means of survival. The changing meaning of other key terms are examined in detail; these include, among others, "forced labor" (Zwangsarbeit), "slave labor" (Sklavenarbeit). The volume carefully analyzes the modus operandi of the Nazi system of power, in which bureaucracy ballooned, there were conflicts of interest between different institutions, and there was a total destruction of human and moral values, which led to extensive degeneration.